Kajian Yuridis Pelaksanaan Aksi Hak Asasi Manusia Kementerian Hukum dan Hak Asasi Manusia - Setiaji Wibowo; Joko Widarto; Markoni Markoni; Wasis Susetio (CV. Syntax Corporation Indonesia, 2023)
Indonesia as a Law State upholds human rights as stated in constitution and law. After Indonesia Reformation, one of the efforts to fulfill human rights by Indonesian Government is stated in National Action Plan for Human Rights (RANHAM) implemented through 5 year phase and is currently on the fifth generation. Each generation has its target and accomplishment based on the development of current human rights issues in Indonesia. RANHAM has a long coverage as a tool to fulfill human rights for its encouragement on the cooperation between ministries and institutions as well as local government (province and district level). This research explains RANHAM success and challenges as mandated by Presidential Regulation Number 53 of 2021 to fulfill human rights for persons with disabilities corresponds with Law Number 39 of 1999 and Law Number 8 of 2016. This research uses normative method by studying material from the secondary sources. Normative research aims to direct, analyze, systemize, interpret, and evaluate positive law. The research shows that the implementation of RANHAM in 2021 is the form of human rights fulfilment by Indonesian Government as its responsibility as written in constitution article 28I section 4 and Indonesian Law of Human Rights Number 39 of 1999. The challenge arises from RANHAM could be mitigated by Regulation of the Minister of Law and Human Rights Number 19 of 2022 and by the policy made by Directorate General of Human Rights as the secretariat of RANHAM national committee. The first recommendation suggests that RANHAM national committee monitor and facilitate the implementation of RANHAM by other Indonesian government institution. The second recommendation suggests that Directorate General of Human Rights could further strengthen its authority to coordinate with other government institution.